Photoluminescence lineshape features of carbon δ-doped GaAs heterostructures - Schuster, J; Kim, T Y; Batke, E; Reuter, Dirk; Wieck, A D (Journal of Physics: Condensed Matter)

Cyclotron-resonant exciton transfer between the nearly free and strongly localized radiative states of a two-dimensional hole gas in a high magnetic field - Bryja, L.; Jadczak, J.; Wójs, A.; Bartsch, G.; Yakovlev, D. R.; Bayer, M.; Plochocka, P.; Potemski, M.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Electron-nuclei spin coupling in GaAs—Free versus localized electrons - Huang, J.; Chen, Y. S.; Ludwig, A.; Reuter, Dirk; Wieck, A. D.; Bacher, G. (Applied Physics Letters)

Probing Single-Charge Fluctuations at aGaAs/AlAsInterface Using Laser Spectroscopy on a Nearby InGaAs Quantum Dot - Houel, J.; Kuhlmann, A. V.; Greuter, L.; Xue, F.; Poggio, M.; Gerardot, B. D.; Dalgarno, P. A.; Badolato, A.; Petroff, P. M.; Ludwig, A.; Reuter, Dirk; Wieck, A. D.; et al. (Physical Review Letters)

Fabrication and characterization of ambipolar devices on an undoped AlGaAs/GaAs heterostructure - Chen, J. C. H.; Wang, D. Q.; Klochan, O.; Micolich, A. P.; Das Gupta, K.; Sfigakis, F.; Ritchie, D. A.; Reuter, Dirk; Wieck, A. D.; Hamilton, A. R. (Applied Physics Letters)

Room temperature spin relaxation in quantum dot based spin-optoelectronic devices - Höpfner, Henning; Li, Mingyuan; Ludwig, Arne; Ludwig, Astrid; Stromberg, Frank; Wende, Heiko; Keune, Werner; Reuter, Dirk; Wieck, Andreas D.; Gerhardt, Nils C.; Hofmann, Martin R. (Ultrafast Phenomena and Nanophotonics XVI)

Intrinsic Spin Fluctuations Reveal the Dynamical Response Function of Holes Coupled to Nuclear Spin Baths in (In,Ga)As Quantum Dots - Li, Yan; Sinitsyn, N.; Smith, D. L.; Reuter, Dirk; Wieck, A. D.; Yakovlev, D. R.; Bayer, M.; Crooker, S. A. (Physical Review Letters)

Scaling coefficient for three-dimensional grain coalescence of ZnO on Si(111) - Ruth, Marcel; Meier, Cedrik (Physical Review B)

Carrier localization in ZnO quantum wires - Kröger, Philipp; Ruth, Marcel; Weber, Nils; Meier, Cedrik (Applied Physics Letters)

Enhanced photoluminescence of colloidal nanocrystals embedded in epitaxially grown semiconductor microstructures - Kampmeier, J.; Rashad, M.; Woggon, U.; Ruth, M.; Meier, Cedrik; Schikora, D.; Lischka, K.; Pawlis, A. (Physical Review B)

Biomimetic approaches to create anti-reflection glass surfaces for solar cells using self-organizing techniques - Achtelik, J.; Sievers, W.; Lindner, Jörg (Materials Science and Engineering: B)
Aiming to diminish the reflection losses of glass covered light harvesting devices, the optical reflectivity of nanostructured glass surfaces is studied theoretically and experimentally. The work is inspired by the nanoscale roughness of insect eyes, which is tried to be replicated on a technical glass surface. To this end, the reflectivity of glass surfaces with topographies represented by linear, parabolic and Fermishaped glass/air fill factor profiles is calculated for normal incidence. It is shown that using the latter ones, an almost complete suppression of reflections can be achieved. A simple, self-organization technique to create such Fermi-shaped filling factor profiles in glass experimentally is also presented.

Formation of defects in cubic GaN grown on nano-patterned 3C-SiC (001) - Kemper, R. M.; Häberlen, M.; Schupp, T.; Weinl, M.; Bürger, M.; Ruth, M.; Meier, Cedrik; Niendorf, T.; Maier, H. J.; Lischka, K.; As, D. J.; Lindner, Jörg (physica status solidi (c))
We report an anisotropic formation of defects in cubic GaN grown on nano-patterned 3C-SiC/Si (001) by molecular beam epitaxy. Nano-patterning of 3C-SiC/Si (001) is achieved by nanosphere lithography and a reactive ion etching process. Atomic force microscopy and scanning electron microscopy show that the selectivearea- grown cubic GaN nucleates in two structurally different domains, which most probably originate from the substrate. In adjacent domains the formation of defects, especially hexagonal inclusions, is different and leads to two different surface morphologies. The dominant phase within these domains was measured by electron backscatter diffraction. Optical properties were investigated by micro-photoluminescence and cathodoluminescence spectroscopy.

Vibrational fingerprints of LiNbO3-LiTaO3 mixed crystals - Sanna, Simone; Riefer, Arthur; Neufeld, Sergej; Schmidt, Wolf Gero; Berth, Gerhard; Widhalm, Alex; Zrenner, Artur (Proceedings of ISAF-ECAPD-PFM 2012)
The structural and vibrational properties of lithium niobate (LN) – lithium tantalate (LT) mixed crystals (LNT, LiNb1-xTaxO3) are investigated over the whole composition range by first-principles simulations. The crystal volume grows roughly linearly from LT to LN, whereby the lattice parameters a and c show minor deviations from the Vegard behavior between the end compounds, LiNbO3 and LiTaO3. Our calculations in the framework of the density functional theory show the TO1, TO2 and TO4-modes to become harder with increasing Nb concentration. TO3 becomes softer with increasing Nb content, instead. The frequency shifts of the zone center A1-TO phonon modes for crystals with different compositions are found to be as large as 30 cm-1. Raman spectroscopy, which is sensitive to the A1 modes, can be therefore employed to determine the crystal composition.
Keywords: Ferroelectrics; Vibrational properties; LiNbO3; LiTaO3; Mixed Crystals

Coherent optoelectronics with quantum dots - Michaelis de Vasconcellos, Steffen; Gordon, Simon; Mantei, Dirk; Leier, Yves Alexander; Al-Hmoud, M.; Quiring, Wadim; Zrenner, Artur (QUANTUM OPTICS WITH SEMICONDUCTOR NANOSTRUCTURES)
Coherent physics and applications of exciton qubits in electric fi eld tunable quantum dot structures are our focus. Excitations with picosecond (ps) laser pulses result in qubit rotations. Using state projection by tunnelling the readout can be performed in quantitative way. As a function of electric fi eld induced detuning Ramsey fringes of a single exciton qubit can be observed and controlled for double pulse excitation. Therefore it is possible to demonstrate voltage controlled qubit manipulations within a wide range of pulse delays. Using fast electric signals, phase-locked to ps-laser pulses, the coherent control of an exciton qubit can be obtained by electric interaction. Such voltage controlled qubit manipulations seem to be essential for new types of optoelectronic quantum gates and novel applications in the fi eld of coherent optoelectronics.
Keywords: excitons; quantum bits; coherent manipulation; Ramsey interference; quantum gate

Dispersionless Phase Discontinuities for Controlling Light Propagation - Huang, Lingling; Chen, Xianzhong; Mühlenbernd, Holger; Li, Guixin; Bai, Benfeng; Tan, Qiaofeng; Jin, Guofan; Zentgraf, Thomas; Zhang, Shuang (Nano Letters)

Mapping the near-field dynamics in plasmon-induced transparency - Ye, Ziliang; Zhang, Shuang; Wang, Yuan; Park, Yong-Shik; Zentgraf, Thomas; Bartal, Guy; Yin, Xiaobo; Zhang, Xiang (Physical Review B)

Compact Magnetic Antennas for Directional Excitation of Surface Plasmons - Liu, Yongmin; Palomba, Stefano; Park, Yongshik; Zentgraf, Thomas; Yin, Xiaobo; Zhang, Xiang (Nano Letters)

Control of plasmon dynamics in coupled plasmonic hybrid mode microcavities - Lanzillotti-Kimura, N. D.; Zentgraf, Thomas; Zhang, X. (Physical Review B)

Slow-light dispersion by transparent waveguide plasmon polaritons - Ishikawa, Atsushi; Oulton, Rupert F.; Zentgraf, Thomas; Zhang, Xiang (Physical Review B)

All-optical tunability of microdisk lasers via photo-adressable polyelectrolyte functionalization - Piegdon, K. A.; Lexow, M.; Grundmeier, G.; Kitzerow, Heinz-Siegfried; Pärschke, K.; Mergel, D.; Reuter, Dirk; Wieck, A. D.; Meier, Cedrik (Optics Express)

All-optical tunability of microdisk lasers via photo-adressable polyelectrolyte functionalization - Piegdon, K. A.; Lexow, M.; Grundmeier, G.; Kitzerow, Heinz-Siegfried; Pärschke, K.; Mergel, D.; Reuter, Dirk; Wieck, A. D.; Meier, C. (Optics Express)

Kinetics of the grating formation in holographic polymer-dispersed liquid crystals: NMR measurement of diffusion coefficients - Tang, Mingxue; Redler, Andreas; Topgaard, Daniel; Schmidt, Claudia; Kitzerow, Heinz-Siegfried (Colloid and Polymer Science)
Keywords: Materials Chemistry; Colloid and Surface Chemistry; Polymers and Plastics; Physical and Theoretical Chemistry

Doping the nematic liquid crystal 5CB with milled BaTiO3nanoparticles - Lorenz, Alexander; Zimmermann, Natalie; Kumar, Satyendra; Evans, Dean R.; Cook, Gary; Kitzerow, Heinz-Siegfried (Physical Review E)
Keywords: Industrial and Manufacturing Engineering; Metals and Alloys; Strategy and Management; Mechanical Engineering

Switching performance of a polymer-stabilized antiferroelectric liquid crystal based on bent-core molecules - Atorf, B.; Hoischen, A.; Ros, M. B.; Gimeno, N.; Tschierske, C.; Dantlgraber, G.; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Electrical fine tuning of liquid crystal lasers - Schmidtke, Jürgen; Jünnemann, Gisela; Keuker-Baumann, Susanne; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Doping a Mixture of Two Smectogenic Liquid Crystals with Barium Titanate Nanoparticles - Lorenz, Alexander; Zimmermann, Natalie; Kumar, Satyendra; Evans, Dean R.; Cook, Gary; Fernández Martínez, Manuel; Kitzerow, Heinz-Siegfried (The Journal of Physical Chemistry B)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Physical and Theoretical Chemistry

Three-dimensional structure in holographic polymer-dispersed liquid crystals - Redler, Andreas; Kitzerow, Heinz-Siegfried (Polymers for Advanced Technologies)
Keywords: Polymers and Plastics

New developments in nanoparticle-liquid crystal composites: from magic-sized semiconductor nanoclusters to alignment pattern formation via nanoparticle stenciling - Mirzaei, Javad; Sawatzky, Ryan; Sharma, Anshul; Urbanski, Martin; Yu, Kui; Kitzerow, Heinz-Siegfried; Hegmann, Torsten (SPIE Proceedings)

Cavity-assisted emission of polarization-entangled photons from biexcitons in quantum dots with fine-structure splitting - Schumacher, Stefan; Förstner, Jens; Zrenner, Artur; Florian, Matthias; Gies, Christopher; Gartner, Paul; Jahnke, Frank (Optics Express)
We study the quantum properties and statistics of photons emitted by a quantum-dot biexciton inside a cavity. In the biexciton-exciton cascade, fine-structure splitting between exciton levels degrades polarization-entanglement for the emitted pair of photons. However, here we show that the polarization-entanglement can be preserved in such a system through simultaneous emission of two degenerate photons into cavity modes tuned to half the biexciton energy. Based on detailed theoretical calculations for realistic quantum-dot and cavity parameters, we quantify the degree of achievable entanglement.
Keywords: tet_topic_qd

Optimization of the intensity enhancement in plasmonic nanoantennas - Hildebrandt, Andre; Reichelt, Matthias; Meier, Torsten; Förstner, Jens
We design the geometrical shape of plasmonic nanostructures to achieve field patterns with desired properties. For this, we combine Maxwell simulations and automatic optimization techniques. By allowing variations of the geometrical shape, which can be based on either boxes or arbitrary polygons, we maximize the desired objective.
Keywords: tet_topic_optical antenna; tet_topic_plasmonics

High resolution time-to-space conversion of sub-picosecond pulses at 155µm by non-degenerate SFG in PPLN crystal - Shayovitz, Dror; Herrmann, Harald; Sohler, Wolfgang; Ricken, Raimund; Silberhorn, Christine; Marom, Dan M. (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Characteristics of displaced single photons attained via higher order factorial moments - Laiho, Kaisa; Avenhaus, Malte; Silberhorn, Christine (New Journal of Physics)
Keywords: General Physics and Astronomy

Collective Effects in Second-Harmonic Generation from Split-Ring-Resonator Arrays - Linden, S.; Niesler, F. B. P.; Förstner, Jens; Grynko, Yevgen; Meier, Torsten; Wegener, M. (Physical Review Letters)
Optical experiments on second-harmonic generation from split-ring-resonator square arrays show a nonmonotonic dependence of the conversion efficiency on the lattice constant. This finding is interpreted in terms of a competition between dilution effects and linewidth or near-field changes due to interactions among the individual elements in the array.
Keywords: tet_topic_shg; tet_topic_meta

Photonic crystal waveguides intersection for resonant quantum dot optical spectroscopy detection - Song, Xiaohong; Declair, Stefan; Meier, Torsten; Zrenner, Artur; Förstner, Jens (Optics Express)
Using a finite-difference time-domain method, we theoretically investigate the optical spectra of crossing perpendicular photonic crystal waveguides with quantum dots embedded in the central rod. The waveguides are designed so that the light mainly propagates along one direction and the cross talk is greatly reduced in the transverse direction. It is shown that when a quantum dot (QD) is resonant with the cavity, strong coupling can be observed via both the transmission and crosstalk spectrum. If the cavity is far off-resonant from the QD, both the cavity mode and the QD signal can be detected in the transverse direction since the laser field is greatly suppressed in this direction. This structure could have strong implications for resonant excitation and in-plane detection of QD optical spectroscopy.
Keywords: tet_topic_phc; tet_topic_qd

Near-field coupling and second-harmonic generation in split-ring resonator arrays - Grynko, Yevgen; Meier, Torsten; Linden, Stefan; Niesler, Fabian B. P.; Wegener, Martin; Förstner, Jens
We simulate the linear and nonlinear optical response from split-ring resonator (SRR) arrays to study collective effects between the constituent SRRs that determine spectral properties of the second harmonic generation (SHG). We apply the Discontinuous Galerkin Time Domain (DGTD) method and the hydrodynamic Maxwell-Vlasov model to calculate the SHG emission. Our model is able to qualitatively reproduce and explain the non-monotonic dependence of the spectral SHG transmission measured experimentally for SRR arrays with different lattice constants
Keywords: tet_topic_meta; tet_topic_shg

Engineering high harmonic generation in semiconductors via pulse shaping - Reichelt, Matthias; Hildebrandt, Andre; Walther, Andrea; Förstner, Jens; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XVI)
Paper Abstract High harmonic generation is investigated for a two-band model of a semiconductor nanostructure. Similar to an atomic two-level system, the semiconductor emits high harmonic radiation. We show how one can specifically enhance the emission for a given frequency by applying a non-trivially shaped laser pulse. Therefore, the semiconductor Bloch equations including the interband and additionally the intraband dynamics are solved numerically and the spectral shape of the input pulse is computed via an optimization algorithm. It is demonstrated that desired emission frequencies can be favored even though the overall input power is kept constant. We also suggest special metallic nano geometries to achieve enhanced localized optical fields. They are found by geometric optimization.
Keywords: tet_topic_shg

Tailoring the high-harmonic emission in two-level systems and semiconductors by pulse shaping - Reichelt, Matthias; Walther, Andrea; Meier, Torsten (Journal of the Optical Society of America B)
The generation of specific high harmonics for an optical two-level system is elucidated. The desired emitted radiation can be induced by a carefully designed excitation pulse, which is found by a multiparameter optimization procedure. The presented mechanism can also be applied to semiconductor structures for which the calculations result in much higher emission frequencies. The optimization procedure is either performed using a genetic algorithm or a rigorous mathematical optimization technique.

A graphene-based broadband optical modulator - Liu, Ming; Yin, Xiaobo; Ulin-Avila, Erick; Geng, Baisong; Zentgraf, Thomas; Ju, Long; Wang, Feng; Zhang, Xiang (Nature)

Towards the Origin of the Nonlinear Response in Hybrid Plasmonic Systems - Utikal, Tobias; Zentgraf, Thomas; Paul, Thomas; Rockstuhl, Carsten; Lederer, Falk; Lippitz, Markus; Giessen, Harald (Physical Review Letters)

Development of Bulk Optical Negative Index Fishnet Metamaterials: Achieving a Low-Loss and Broadband Response Through Coupling - Valentine, Jason; Zhang, Shuang; Zentgraf, Thomas; Zhang, Xiang (Proceedings of the IEEE)

Plasmonic Luneburg and Eaton lenses - Zentgraf, Thomas; Liu, Yongmin; Mikkelsen, Maiken H.; Valentine, Jason; Zhang, Xiang (Nature Nanotechnology)

The influence of charged InAs quantum dots on the conductance of a two-dimensional electron gas: Mobility vs. carrier concentration - Marquardt, B.; Beckel, A.; Lorke, A.; Wieck, A. D.; Reuter, Dirk; Geller, M. (Applied Physics Letters)

Many-body enhanced nonlinear conductance resonance in quantum channels - Han, Jong E.; Fischer, Saskia F.; Buchholz, Sven S.; Kunze, Ulrich; Reuter, Dirk; Wieck, Andreas D.; Bird, Jonathan P. (Physical Review B)

Dynamic Nuclear Spin Resonance inn-GaAs - Chen, Y. S.; Reuter, Dirk; Wieck, A. D.; Bacher, G. (Physical Review Letters)

Optical Control of Coherent Interactions between Electron Spins in InGaAs Quantum Dots - Spatzek, S.; Greilich, A.; Economou, Sophia E.; Varwig, S.; Schwan, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Reinecke, T. L.; Bayer, M. (Physical Review Letters)

Generation and detection of mode-locked spin coherence in (In,Ga)As/GaAs quantum dots by laser pulses of long duration - Spatzek, S.; Varwig, S.; Glazov, M. M.; Yugova, I. A.; Schwan, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Edge-induced magnetoplasmon excitation in a two-dimensional electron gas under quantum Hall conditions - Notthoff, Christian; Reuter, Dirk; Wieck, Andreas D.; Lorke, Axel (Physical Review B)

Resonant nuclear spin pumping in (In,Ga)As quantum dots - Cherbunin, R. V.; Flisinski, K.; Gerlovin, I. Ya.; Ignatiev, I. V.; Kuznetsova, M. S.; Petrov, M. Yu.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Electrostatically trapping indirect excitons in coupled InxGa1−xAs quantum wells - Schinner, G. J.; Schubert, E.; Stallhofer, M. P.; Kotthaus, J. P.; Schuh, D.; Rai, A. K.; Reuter, Dirk; Wieck, A. D.; Govorov, A. O. (Physical Review B)

Polarization-preserving confocal microscope for optical experiments in a dilution refrigerator with high magnetic field - Sladkov, Maksym; Bakker, M. P.; Chaubal, A. U.; Reuter, Dirk; Wieck, A. D.; van der Wal, C. H. (Review of Scientific Instruments)